Topical systems for the controlled release of antineoplastic drugs: oxidized alginate-gelatin hydrogel/unilamellar vesicles - Stagnoli, Soledad; Garro, Cintia; Ertekin, Ozlem; Heid, Susanne; Seyferth, Stefan; Soria, Gastón; Mariano Correa, N.; Leal-Egaña, Aldo; Boccaccini, Aldo R. (Journal of colloid and interface science, 2022)
The efficacy of chemotherapeutic procedures relies on delivering proper concentrations of anti-cancer drugs in the tumor surroundings, so as to prevent potential side effects on healthy tissues. Novel drug carrier platforms should not just be able to deliver anticancer molecules, but also allow for adjustements in the way these drugs are administered to the patients. We developed a system for delivering water-insoluble drugs, based on the use of 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), or bis(2-ethylhexyl) sulfosuccinate benzyl-n-hexadecyldimethylammonium (BHD-AOT), embedded into oxidized alginate-gelatin (ADA/Gel) hydrogel, emulating a patch for topic applications. After being loaded with curcumin, cancer cells such as human colorectal adenocarcinoma (HCT116 and DLD-1) and melanoma cell lines (MEL501), and non-malignant cells such as mammary epithelial cell lines (NMuMG) and embryonal fibroblasts (NIH 3T3 or NEO cells) were analyzed for biocompatibility and cytotoxic effects.